2017
DOI: 10.1590/0102-6720201700030008
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Can Prevent Hepatic Remote Reperfusion Injury

Abstract: Background:Some studies have shown that statins have a promising effect on protection against reperfusion injury. Aim:To evaluate the ability of ischemic postconditioning, statins and both associated to prevent or minimize reperfusion injury in the liver of rats subjected to ischemia and reperfusion by abdominal aorta clamping. Method:Were used 41 Wistar rats, which were distributed into five groups: ischemia and reperfusion (I/R), ischemic postcondictioning (IPC), postconditioning + statin (IPC+S), statin (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Those authors also reported moderate inflammation in hepatic parenchyma. [ 31 ] Şimşek et al created an I/R model by clamping the infrarenal aorta and observed vacuolar degeneration and vascular congestion. [ 32 ] Similar to those two studies, we observed necrosis in hepatocytes and edematous areas in the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors also reported moderate inflammation in hepatic parenchyma. [ 31 ] Şimşek et al created an I/R model by clamping the infrarenal aorta and observed vacuolar degeneration and vascular congestion. [ 32 ] Similar to those two studies, we observed necrosis in hepatocytes and edematous areas in the hepatic parenchyma.…”
Section: Discussionmentioning
confidence: 99%